High-strength and high-toughness foamed ceramic and preparation method thereof
By introducing cyclosilicon resin and closed-cell foam into the foam ceramic material and performing multi-stage sintering, open-cell foam ceramic materials with high strength, high toughness and stable connection were prepared, and the existing materials were solved at high temperatures. Problems of unstable connections in high-voltage environments.
Patent Information
- Application Number
- CN202411694126.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-14
AI Technical Summary
In high-temperature and high-pressure environments, the material properties are affected due to the unstable connection between multi-layer structures.
By mixing materials such as silicon carbide, silicate, clay and foaming agent, and adding sodium carboxymethylcellulose and sodium hydroxide aqueous solution for ball milling, after obtaining the initial powder, cyclosilicon resin is added for low-temperature sintering. , an open pore base material is formed, and then mixed with the closed-cell foam and sintered at high temperature to prepare a foam ceramic material with open pore and closed-cell structure.
The high strength and toughness of open-cell foam ceramic materials are achieved, which solves the problem of unstable connection of multi-layer materials, and maintains good performance in high-temperature and high-pressure environments.
Smart Images

Figure BDA0005151712260000131 
Figure BDA0005151712260000141 
Figure BDA0005151712260000151
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of foam ceramic materials, and in particular to a high-strength and high-toughness foam ceramic and a preparation method thereof. Background Art
[0002] Foam ceramics are a new type of lightweight material, mainly made of glass and ceramic materials. They have a porous structure and can withstand high temperatures and high pressures. They are widely used in aerospace, automobile manufacturing, construction and other fields. Foam ceramics can generally be divided into two categories: open-cell (net-shaped) ceramic materials and closed-cell ceramic materials, mainly based on whether each hole has a solid wall. If the solid that forms the foam is only contained in the pores, it is called an open-cell ceramic material, and its pores are interconnected; if there is a solid wall, the foam is called a closed-cell ceramic material, and the pores are separated from each other by a continuous ceramic matrix.
[0003] Due to the structural characteristics of open-cell ceramic materials, their density is low, and their strength and toughness are poor; while the use of closed-cell ceramic materials has many pores, resulting in excessive heat transfer and poor heat absorption. In this regard, the patent with publication number CN117945781A provides a heat storage-insulation multifunctional ceramic and its preparation method, which sets a double-layer ceramic containing both open and closed pores to take into account the heat storage and insulation of open-cell ceramics and the high strength and toughness of closed-cell ceramics.
[0004] However, the existing method of arranging multiple layers of ceramic materials to achieve the performance of both open-pore ceramics and closed-pore ceramics as mentioned above has the problem of poor connection stability between the multilayer structures in practical applications, which will have a certain impact on the material properties. Summary of the invention
[0005] The technical problems to be solved by the present invention are:
[0006] In order to achieve good heat storage and heat preservation and high strength and toughness in the existing foam ceramic materials, a multilayer ceramic is proposed by combining an open-cell ceramic layer material with a closed-cell ceramic layer material. Each layer of material can exert its own beneficial properties, thereby showing an advantage of outstanding comprehensive performance as a whole. However, during use, the above-mentioned materials are easily unstable in connection and combination between each layer of material due to the influence of complex environments such as high temperature and high pressure, which affects the material performance.
[0007] The technical solution adopted by the present invention is:
[0008] The present invention provides a method for preparing high-strength and high-toughness foam ceramics, comprising the following steps:
[0009] S1: silicon carbide, silicate, clay rock, and foaming agent are mixed, and then sodium carboxymethyl cellulose and sodium hydroxide aqueous solution are added, mixed, ball-milled, dried, finely ground, and sieved to obtain primary powder;
[0010] S2 takes a cyclosilicone-based resin, adds it to the initial powder, places it in an environment of 150-320°C, and sinters it at low temperature to obtain an open-pore base material;
[0011] S3: taking a closed-cell foam, adding it to an open-cell base material, mixing it evenly, pressing it into a blank, placing it in an environment of 500-950° C., and sintering it at high temperature to obtain the foam ceramic.
[0012] Preferably, in step S3, the closed-cell foam is prepared as follows:
[0013] Take quartz sand, sodium feldspar, potassium feldspar, carbon powder and zinc oxide, add foaming agent and solvent, press into blanks, sinter at 720-750° C., cool to room temperature, and grind roughly to obtain the closed-cell foam.
[0014] Preferably, the mass ratio of quartz sand, sodium feldspar, potassium feldspar, carbon powder and zinc oxide is 25-35:2.5-3:2.5-3:1.3-1.6:2.3-2.8.
[0015] Preferably, the closed-cell foam has a particle size of 0.35-2.25 mm.
[0016] Preferably, in step S2, the preparation method of the cyclosiloxy resin is as follows:
[0017] The trifunctional silane and the emulsifier are mixed, added into an organic solvent, and stirred under pressure; azobisisobutyronitrile is then added, heated for reaction, and then filtered, washed, and centrifuged in sequence to obtain the cyclosiloxy resin.
[0018] Preferably, in step S3, multi-stage sintering is adopted during sintering.
[0019] Preferably, the high temperature sintering process includes:
[0020] One-stage sintering, keeping at 500-550℃ for 10-20min;
[0021] Second stage sintering, keep at 650-700℃ for 10-20min;
[0022] Three-stage sintering, keeping at 800-850℃ for 10-20min.
[0023] Preferably, in step S1, the solid-liquid ratio is controlled to be 1:0.5-1.5 during ball milling, and the particle size of the raw material after ball milling is 1-5 mm; after fine grinding, it is sieved through 80-120 mesh.
[0024] The beneficial effects of the present invention are as follows:
[0025] The present invention provides a foam ceramic composite material having both an open-cell structure and a closed-cell structure. A closed-cell foam body is introduced into an open-cell ceramic substrate to form an open-cell-closed-cell foam ceramic material with a higher degree of interaction and a greater bonding strength, so as to solve the problem of unstable connection and bonding between layered materials existing in multi-layer stacked open-cell-closed-cell materials. The material has excellent performance in strength, toughness and other properties, and can meet more diversified application needs.
[0026] Generally, when the porosity decreases, the fracture points per unit area on the fracture surface of the porous ceramic material increase, and the bending strength increases, that is, the increase in porosity will cause the problem of reduced strength. However, during the preparation process of the foam ceramic of the present invention, when the open-cell base material contacts the closed-cell foam body, a large amount of it can be attached to the surface of the closed-cell foam body, and after sintering the pressed green sheet, a stable bonding stress is formed. The base material of the open-cell structure is mainly distributed on the surface of the closed-cell foam body, which can form a higher porosity on the surface of the material, and the closed-cell foam body filled in the material can effectively maintain the strength of the material, thereby achieving material properties that take into account both high porosity and high strength.
[0027] Among them, a resin material containing a cyclosiloxy structure is introduced into the initial powder that can form an open-cell structure as a molecular aggregate with a spatial three-dimensional structure, so that the open-cell base material has a more stable structural morphology with higher porosity, and in the subsequent process of introducing a closed-cell foam, the closed-cell foam can be stably bridged to the open-cell base material with a spatial network structure during the multi-stage sintering process, maintaining a high degree of cross-linking between the open-cell base material and the closed-cell foam, so as to improve the comprehensive performance of the material and maintain a high stability. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0029] The present invention provides a high-strength and high-toughness foam ceramic, and the preparation method thereof comprises the following steps:
[0030] (1) Silicon carbide, silicate, clay rock and foaming agent are mixed according to the amount, sodium carboxymethyl cellulose and sodium hydroxide aqueous solution are added and mixed, and wet ball milling is performed. During ball milling, the solid-liquid ratio is controlled to be 1:0.5-1.5, and ceramic balls are used as ball milling media. The raw materials are ball milled to 1-5 mm; then, the raw materials are filtered, dried at a low temperature of 25-40° C., and then finely ground. The raw materials are sieved through 80-120 mesh to obtain primary powder, which is stored for later use.
[0031] (2) Adding cyclosilicone-based resin to the primary powder, placing it in an environment of 150-320° C., performing low-temperature sintering, and keeping the temperature for 20-30 minutes to obtain an open-pore base material.
[0032] (3) Adding closed-cell foam to the open-cell base material, stirring and mixing, pressing into a blank, placing it in an environment of 500-950°C for high-temperature sintering, and then cooling it to room temperature to obtain a foam ceramic material.
[0033] In the present invention, during high temperature sintering, gradient temperature is used for graded sintering, such as sintering at 500-550°C, 650-700°C, and 800-850°C respectively, each of which is kept warm for 10-20 minutes.
[0034] In the present invention, the cyclosiloxy resin added to the primary powder is prepared by the following steps:
[0035] Take trifunctional silane, such as trichlorosilane or trialkoxysilane, mix with an emulsifier, add to an organic solvent, place under a pressure of 150-200 MPa, and stir and homogenize; add azobisisobutyronitrile, heat to 60-80°C, react for 1-3.5 hours, and then filter, wash, and centrifuge in sequence to obtain a cyclosiloxy resin;
[0036] Among them, the emulsifier can be sodium dodecyl sulfate, octylphenoxy polyether alcohol or polysorbate, and the organic solvent can be ethanol, isopropanol, acetone or diethyl ether.
[0037] Those skilled in the art may also directly select other existing resin materials containing cyclosilyl structures as molecular aggregates with a three-dimensional spatial structure to maintain the thermal insulation and other effects of the material.
[0038] In the present invention, the closed-cell foam added to the open-cell base material has an average particle size of about 0.35-2.25 mm, and the preparation method thereof comprises the following steps:
[0039] Take quartz sand, sodium feldspar, potassium feldspar, carbon powder and zinc oxide, add a foaming agent (such as calcium carbonate) and a solvent (such as borax), press them into billets, sinter them at 720-750°C, cool them to room temperature, and grind them roughly to a particle size of about 0.35-2.25 mm, which is a closed-cell foam.
[0040] The high-strength and high-toughness foam ceramic in the present invention includes an open-cell ceramic substrate, and a closed-cell foam body is introduced into the open-cell ceramic substrate to form an open-cell-closed-cell foam ceramic material with a higher degree of interaction and greater bonding strength, so as to solve the problem of unstable connection and bonding between layered materials existing in multi-layer stacked open-cell-closed-cell materials.
[0041] Example 1
[0042] Step 1: Take 40.2g of silicon carbide, 28.6g of organic silicate, 10g of clay rock and 5.5g of foaming agent respectively, mix them, then add 1.5g of sodium carboxymethyl cellulose and 35% sodium hydroxide aqueous solution, stir and mix, control the solid-liquid ratio to 1:0.8, use ceramic balls as ball milling media, perform wet ball milling, and ball mill the raw materials into 1.25±0.25mm granular powder; then filter to remove water and solvent, place at 35°C for low temperature drying, then fine grind, and pass through a 100-mesh sieve to obtain a primary powder, which is vacuum stored for later use.
[0043] Step 2: Take 25g of trichlorosilane and 4.64g of sodium dodecyl sulfate, mix them, add them to 50mL of isopropanol, pressurize them to 160MPa and stir; then add 3.5g of azobisisobutyronitrile, add them to 70°C, react for 2h, and after the reaction is completed, filter, wash and centrifuge them in sequence to obtain a cyclosiloxy resin, which is stored for later use.
[0044] Step 3: Take 35g of quartz sand, 3g of sodium feldspar, 3g of potassium feldspar, 1.5g of carbon powder and 2.71g of zinc oxide, mix them, and add 8.5g of calcium carbonate and 5.2g of borax, mix them, press them into billets, sinter them at 720°C for 2.5h, then cool them to room temperature, and grind them into coarse granular powder with a particle size of about 1.25mm to obtain a closed-cell foam, which is stored for later use.
[0045] Step 4: Add the cyclosilicone resin prepared above to the initial powder, place it at 230°C, and sinter it at low temperature for 25 minutes to obtain an open-cell base material; then add the closed-cell foam, stir and mix, press it into a blank, and place it in a temperature environment of 500-550°C, 650-700°C, and 800-850°C in turn, sinter it at each temperature environment for 15 minutes, and then cool it to room temperature to obtain a composite foam ceramic material.
[0046] Example 2
[0047] Step 1: Take 40.2g of silicon carbide, 28.6g of organic silicate, 10g of clay rock and 5.5g of foaming agent respectively, mix them, then add 1.5g of sodium carboxymethyl cellulose and 35% sodium hydroxide aqueous solution, stir and mix, control the solid-liquid ratio to 1:0.8, use ceramic balls as ball milling media, perform wet ball milling, and ball mill the raw materials into 1.25±0.25mm granular powder; then filter to remove water and solvent, place at 35°C for low temperature drying, then fine grind, and pass through a 100-mesh sieve to obtain a primary powder, which is vacuum stored for later use.
[0048] Step 2: Take 12g of trichlorosilane and 2.2g of sodium dodecyl sulfate, mix them, add them to 50mL of isopropanol, pressurize them to 160MPa and stir; then add 2g of azobisisobutyronitrile, heat to 70°C, react for 2h, and after the reaction is completed, filter, wash and centrifuge in sequence to obtain a cyclosiloxy resin, which is stored for later use.
[0049] Step 3: Take 35g of quartz sand, 3g of sodium feldspar, 3g of potassium feldspar, 1.5g of carbon powder and 2.71g of zinc oxide, mix them, and add 8.5g of calcium carbonate and 5.2g of borax, mix them, press them into billets, sinter them at 720°C for 2.5h, then cool them to room temperature, and grind them into coarse granular powder with a particle size of about 1.25mm to obtain a closed-cell foam, which is stored for later use.
[0050] Step 4: Add the cyclosilicone resin prepared above to the initial powder, place it at 230°C, and sinter it at low temperature for 25 minutes to obtain an open-cell base material; then add the closed-cell foam, stir and mix, press it into a blank, and place it in a temperature environment of 500-550°C, 650-700°C, and 800-850°C in turn, sinter it at each temperature environment for 15 minutes, and then cool it to room temperature to obtain a composite foam ceramic material.
[0051] Example 3
[0052] Step 1: Take 28.7g of silicon carbide, 16g of organic silicate, 7.4g of clay rock and 4.1g of foaming agent respectively, mix them, then add 1.05g of sodium carboxymethyl cellulose and 35% sodium hydroxide aqueous solution, stir and mix, control the solid-liquid ratio to 1:0.8, use ceramic balls as ball milling media, perform wet ball milling, and ball mill the raw materials into 1.5±0.25mm granular powder; then filter to remove water and solvent, place at 35°C for low temperature drying, then fine grind, and pass through a 100-mesh sieve to obtain a primary powder, which is vacuum stored for standby use.
[0053] Step 2: Take 25g of trichlorosilane and 4.64g of sodium dodecyl sulfate, mix them, add them to 50mL of isopropanol, pressurize them to 160MPa and stir; then add 3.5g of azobisisobutyronitrile, add them to 70°C, react for 2h, and after the reaction is completed, filter, wash and centrifuge them in sequence to obtain a cyclosiloxy resin, which is stored for later use.
[0054] Step 3: Take 35g of quartz sand, 3g of sodium feldspar, 3g of potassium feldspar, 1.5g of carbon powder and 2.71g of zinc oxide, mix them, and add 8.5g of calcium carbonate and 5.2g of borax, mix them, press them into billets, sinter them at 720°C for 2.5h, then cool them to room temperature, and grind them into coarse granular powder with a particle size of about 1.25mm to obtain a closed-cell foam, which is stored for later use.
[0055] Step 4: Add the cyclosilicone resin prepared above to the initial powder, place it at 230°C, and sinter it at low temperature for 25 minutes to obtain an open-cell base material; then add the closed-cell foam, stir and mix, press it into a blank, and place it in a temperature environment of 500-550°C, 650-700°C, and 800-850°C in turn, sinter it at each temperature environment for 15 minutes, and then cool it to room temperature to obtain a composite foam ceramic material.
[0056] Example 4
[0057] Step 1: Take 40.2g of silicon carbide, 28.6g of organic silicate, 10g of clay rock and 5.5g of foaming agent respectively, mix them, then add 1.5g of sodium carboxymethyl cellulose and 35% sodium hydroxide aqueous solution, stir and mix, control the solid-liquid ratio to 1:0.8, use ceramic balls as ball milling media, perform wet ball milling, and ball mill the raw materials into 1.25±0.25mm granular powder; then filter to remove water and solvent, place at 35°C for low temperature drying, then fine grind, and pass through a 100-mesh sieve to obtain a primary powder, which is vacuum stored for later use.
[0058] Step 2: Take 25g of trichlorosilane and 4.64g of sodium dodecyl sulfate, mix them, add them to 50mL of isopropanol, pressurize them to 160MPa and stir; then add 3.5g of azobisisobutyronitrile, add them to 70°C, react for 2h, and after the reaction is completed, filter, wash and centrifuge them in sequence to obtain a cyclosiloxy resin, which is stored for later use.
[0059] Step 3: Take 25g of quartz sand, 2.8g of sodium feldspar, 2.7g of potassium feldspar, 1.5g of carbon powder and 2.4g of zinc oxide, mix them, and add 8g of calcium carbonate and 3.5g of borax, mix them, press them into billets, sinter them at 720°C for 2.5h, then cool them to room temperature, and grind them into coarse granular powder with a particle size of about 1.25mm to obtain a closed-cell foam, which is stored for later use.
[0060] Step 4: Add the cyclosilicone resin prepared above to the initial powder, place it at 230°C, and sinter it at low temperature for 25 minutes to obtain an open-cell base material; then add the closed-cell foam, stir and mix, press it into a blank, and place it in a temperature environment of 500-550°C, 650-700°C, and 800-850°C in turn, sinter it at each temperature environment for 15 minutes, and then cool it to room temperature to obtain a composite foam ceramic material.
[0061] Example 5
[0062] Step 1: Take 40.2g of silicon carbide, 28.6g of organic silicate, 10g of clay rock and 5.5g of foaming agent respectively, mix them, then add 1.5g of sodium carboxymethyl cellulose and 35% sodium hydroxide aqueous solution, stir and mix, control the solid-liquid ratio to 1:0.8, use ceramic balls as ball milling media, perform wet ball milling, and ball mill the raw materials into 1.25±0.25mm granular powder; then filter to remove water and solvent, place at 35°C for low temperature drying, then fine grind, and pass through a 100-mesh sieve to obtain a primary powder, which is vacuum stored for later use.
[0063] Step 2: Take 25g of trichlorosilane and 4.64g of sodium dodecyl sulfate, mix them, add them to 50mL of isopropanol, pressurize them to 160MPa and stir; then add 3.5g of azobisisobutyronitrile, add them to 70°C, react for 2h, and after the reaction is completed, filter, wash and centrifuge them in sequence to obtain a cyclosiloxy resin, which is stored for later use.
[0064] Step 3: Take 35g of quartz sand, 3g of sodium feldspar, 3g of potassium feldspar, 1.5g of carbon powder and 2.71g of zinc oxide, mix them, and add 8.5g of calcium carbonate and 5.2g of borax, mix them, press them into billets, sinter them at 720°C for 2.5h, then cool them to room temperature, and grind them into coarse granular powder with a particle size of about 1.25mm to obtain a closed-cell foam, which is stored for later use.
[0065] Step 4: Add the cyclosilicone resin prepared above to the initial powder, place it at 230°C, and sinter it at low temperature for 25 minutes to obtain an open-cell base material; then add the closed-cell foam, stir and mix, press it into a blank, and place it in a temperature environment of 550-600°C and 780-830°C in turn, sinter it at each temperature environment for 15 minutes, and then cool it to room temperature to obtain a composite foam ceramic material.
[0066] Example 6
[0067] Step 1: Take 40.2g of silicon carbide, 28.6g of organic silicate, 10g of clay rock and 5.5g of foaming agent respectively, mix them, then add 1.5g of sodium carboxymethyl cellulose and 35% sodium hydroxide aqueous solution, stir and mix, control the solid-liquid ratio to 1:0.8, use ceramic balls as ball milling media, perform wet ball milling, and ball mill the raw materials into 1.25±0.25mm granular powder; then filter to remove water and solvent, place at 35°C for low temperature drying, then fine grind, and pass through a 100-mesh sieve to obtain a primary powder, which is vacuum stored for later use.
[0068] Step 2: Take 25g of trichlorosilane and 4.64g of sodium dodecyl sulfate, mix them, add them to 50mL of isopropanol, pressurize them to 160MPa and stir; then add 3.5g of azobisisobutyronitrile, add them to 70°C, react for 2h, and after the reaction is completed, filter, wash and centrifuge them in sequence to obtain a cyclosiloxy resin, which is stored for later use.
[0069] Step 3: Take 35g of quartz sand, 3g of sodium feldspar, 3g of potassium feldspar, 1.5g of carbon powder and 2.71g of zinc oxide, mix them, and add 8.5g of calcium carbonate and 5.2g of borax, mix them, press them into billets, sinter them at 720°C for 2.5h, then cool them to room temperature, and grind them into coarse granular powder with a particle size of about 1.25mm to obtain a closed-cell foam, which is stored for later use.
[0070] Step 4: Add the cyclosilicone resin prepared above to the primary powder, place it at 320°C, sinter it for 25 minutes, and obtain an open-cell base material; then add the closed-cell foam, stir and mix, press it into a blank, and place it in a temperature environment of 500-550°C, 650-700°C, and 800-850°C in turn, sinter it at each temperature environment for 15 minutes, and then cool it to room temperature to obtain a composite foam ceramic material.
[0071] Comparative Example 1
[0072] Step 1: Take 40.2g of silicon carbide, 28.6g of organic silicate, 10g of clay rock and 5.5g of foaming agent respectively, mix them, then add 1.5g of sodium carboxymethyl cellulose and 35% sodium hydroxide aqueous solution, stir and mix, control the solid-liquid ratio to 1:0.8, use ceramic balls as ball milling media, perform wet ball milling, and ball mill the raw materials into 1.25h±0.25mm granular powder; then filter to remove water and solvent, place at 35°C for low temperature drying, then fine grind, and pass through a 100-mesh sieve to obtain a primary powder, which is vacuum stored for later use.
[0073] Step 2: Take 35g of quartz sand, 3g of sodium feldspar, 3g of potassium feldspar, 1.5g of carbon powder and 2.71g of zinc oxide, mix them, and add 8.5g of calcium carbonate and 5.2g of borax, mix them, press them into billets, sinter them at 720°C for 2.5h, then cool them to room temperature, and grind them into coarse granular powder with a particle size of about 1.25mm to obtain a closed-cell foam, which is stored for later use.
[0074] Step 3: Add closed-cell foam to the primary powder prepared above, stir and mix, and press into a blank, place it in a temperature environment of 500-550℃, 650-700℃, and 800-850℃ in sequence, sinter for 15 minutes at each temperature environment, and then cool to room temperature to obtain a composite foam ceramic material.
[0075] Comparative Example 2
[0076] Step 1: Take 40.2g of silicon carbide, 28.6g of organic silicate, 10g of clay rock and 5.5g of foaming agent respectively, mix them, then add 1.5g of sodium carboxymethyl cellulose and 35% sodium hydroxide aqueous solution, stir and mix, control the solid-liquid ratio to 1:0.8, use ceramic balls as ball milling media, perform wet ball milling, and ball mill the raw materials into 1.25h±0.25mm granular powder; then filter to remove water and solvent, place at 35°C for low temperature drying, then fine grind, and pass through a 100-mesh sieve to obtain a primary powder, which is vacuum stored for later use.
[0077] Step 2: Take 25g of trichlorosilane and 4.64g of sodium dodecyl sulfate, mix them, add them to 50mL of isopropanol, pressurize them to 160MPa and stir; then add 3.5g of azobisisobutyronitrile, add them to 70°C, react for 2h, and after the reaction is completed, filter, wash and centrifuge them in sequence to obtain a cyclosiloxy resin, which is stored for later use.
[0078] Step 3: Take 35g of quartz sand, 3g of sodium feldspar, 3g of potassium feldspar, 1.5g of carbon powder and 2.71g of zinc oxide, mix them, and add 8.5g of calcium carbonate and 5.2g of borax, mix them, press them into billets, sinter them at 720℃ for 2.5h, and then cool them to room temperature to obtain closed-cell foam boards, which are stored for later use.
[0079] Step 4: Add the cyclosilicone resin prepared above to the initial powder, mix well, press into a plate, and then place it at 230°C for low-temperature sintering for 25 minutes to obtain an open-pored plate; alternately stack the open-pored plate and the closed-pored foam plate, press them, and then place them in a temperature environment of 500-550°C, 650-700°C, and 800-850°C in turn, sinter them at each temperature environment for 15 minutes, and then cool them to room temperature to obtain a composite foam ceramic material.
[0080] Comparative Example 3
[0081] Step 1: Take 40.2g of silicon carbide, 28.6g of organic silicate, 10g of clay rock and 5.5g of foaming agent respectively, mix them, then add 1.5g of sodium carboxymethyl cellulose and 35% sodium hydroxide aqueous solution, stir and mix, control the solid-liquid ratio to 1:0.8, use ceramic balls as ball milling media, perform wet ball milling, and ball mill the raw materials into 1.25h±0.25mm granular powder; then filter to remove water and solvent, place at 35°C for low temperature drying, then fine grind, and pass through a 100-mesh sieve to obtain a primary powder, which is vacuum stored for later use.
[0082] Step 2: Take 35g of quartz sand, 3g of sodium feldspar, 3g of potassium feldspar, 1.5g of carbon powder and 2.71g of zinc oxide, mix them, and add 8.5g of calcium carbonate and 5.2g of borax, mix them, press them into billets, sinter them at 720℃ for 2.5h, and then cool them to room temperature to obtain closed-cell foam boards, which are stored for later use.
[0083] Step 3: Alternately stack the open-pore plate and the closed-pore foam plate prepared above, press them, and then place them in a temperature environment of 500-550°C, 650-700°C, and 800-850°C in turn, sinter them for 15 minutes in each temperature environment, and then cool them to room temperature to obtain a composite foam ceramic material.
[0084] Test example
[0085] Samples: Examples 1-6, Comparative Examples 1-3
[0086] (1) Thermal insulation performance test
[0087] According to GB / T 10294-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Insulating Materials", the thermal conductivity of the above samples was measured, and the results are summarized in Table 1 below:
[0088] Table 1 Test results of thermal insulation performance of different samples
[0089]
[0090] (2) Strength and toughness test
[0091] According to GB / T 5486-2008 "Test methods for inorganic rigid thermal insulation products" and GB / T23806-2009 "Test methods for fracture toughness of fine ceramics", the strength and toughness of the above samples were measured respectively. The test results are summarized in Table 2 below:
[0092] Table 2 Mechanical properties of different samples
[0093] sample Compressive strength MPa Flexural strength MPa Fracture toughness MPa / m Example 1 13.07 2.92 11.96 Example 2 13.02 2.89 11.15 Example 3 13.08 2.91 11.67 Example 4 12.94 2.75 11.05 Example 5 12.98 2.84 11.12 Example 6 13.00 2.85 10.93 Comparative Example 1 12.43 2.70 7.99 Comparative Example 2 12.66 2.71 9.17 Comparative Example 3 12.07 2.58 7.24
[0094] (3) High temperature stability test
[0095] Take the above samples separately, place them at 500℃ for 15 minutes, take them out and cool them to room temperature, and measure the thermal conductivity and strength after treatment; take another sample, place it in 8mol / L concentrated nitric acid solution for 15 minutes, take it out and wash and dry it, and measure the thermal conductivity and strength after treatment. The material properties of the samples treated in high temperature or strong acid environment are summarized in the following Tables 3 and 4:
[0096] Table 3 Test results of material properties of samples treated at high temperature
[0097]
[0098] Table 4 Results of material properties of samples treated in strong acid environment
[0099]
[0100] From the sample material performance results measured in Tables 1 to 4 above, it can be seen that the foam ceramic materials prepared in Examples 1 to 6 show good performance advantages in terms of thermal insulation and mechanical strength, and can also maintain relatively stable performance under extreme environments of high temperature or strong acid, while the performance of the composite materials using multi-layer stacking in Comparative Examples 2 to 3 shows a significant decrease. Therefore, it can be explained that the foam ceramics proposed in the present invention can take into account various performance advantages and still maintain relatively stable performance under extreme use conditions.
[0101] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing high-strength and high-toughness foam ceramics, characterized in that: The steps include: S1: silicon carbide, silicate, clay rock, and foaming agent are mixed, and then sodium carboxymethyl cellulose and sodium hydroxide aqueous solution are added, mixed evenly, ball-milled, dried, finely ground, and sieved to obtain primary powder; S2 takes a cyclosilicone-based resin, adds it to the initial powder, and sinters it in an environment of 150-320°C to obtain an open-pore base material; S3: taking the closed-cell foam, adding it to the open-cell base material, mixing it evenly, pressing it into a blank, and sintering it in an environment of 500-950° C. to obtain the foam ceramic.
2. The method for preparing high-strength and high-toughness foam ceramic according to claim 1, characterized in that: In step S3, the closed-cell foam is prepared as follows: Take quartz sand, sodium feldspar, potassium feldspar, carbon powder and zinc oxide, add foaming agent and solvent, press into blanks, sinter at 720-750° C., cool to room temperature, and grind roughly to obtain the closed-cell foam.
3. The method for preparing high-strength and high-toughness foam ceramic according to claim 2, characterized in that: The mass ratio of quartz sand, sodium feldspar, potassium feldspar, carbon powder and zinc oxide is 25-35:2.5-3:2.5-3:1.3-1.6:2.3-2.
8.
4. The method for preparing high-strength and high-toughness foam ceramic according to claim 2, characterized in that: The closed-cell foam has a particle size of 0.35-2.25 mm.
5. The method for preparing high-strength and high-toughness foam ceramic according to claim 1, characterized in that: In step S2, the preparation method of the cyclosiloxy resin is as follows: The trifunctional silane and the emulsifier are mixed, added into an organic solvent, and stirred under pressure; azobisisobutyronitrile is then added, heated for reaction, and then filtered, washed, and centrifuged in sequence to obtain the cyclosiloxy resin.
6. The method for preparing high-strength and high-toughness foam ceramic according to claim 1, characterized in that: In step S3, during sintering, multi-stage sintering is adopted.
7. The method for preparing high-strength and high-toughness foam ceramic according to claim 6, characterized in that: The high temperature sintering process includes: One-stage sintering, keeping at 500-550℃ for 10-20min; Second stage sintering, keep at 650-700℃ for 10-20min; Three-stage sintering, keeping at 800-850℃ for 10-20min.
8. A high-strength and high-toughness foam ceramic, characterized in that: The preparation method is described in any one of claims 1 to 7.
Citation Information
Patent Citations
Heat storage-heat insulation multifunctional ceramic and preparation method thereof
CN117945781A